Analysis of the Handling of Election Violations at TPS 19 Waykandis by Bawaslu and Gakkumdu of Bandarlampung City - Abdul Halim; Hikmah Nur Azizah; Feni Sundari; Mega Astuti; Windy Adelia (JUSTICES: Journal of Law, 2025)
Handling election violations is the primary responsibility of the Election Supervisory Agency (Bawaslu) in maintaining the integrity of democracy. This study discusses the case registration process of alleged violations at Polling Station (TPS) 19 Waykandis by Bawaslu of Bandarlampung City to the Integrated Law Enforcement Center (Gakkumdu), although the report does not explicitly specify the violation points. The purpose of this study is to analyze the legal and administrative procedures carried out by Bawaslu in handling this case, as well as to assess its implications for the election law enforcement process at the regional level. The research method uses a descriptive qualitative approach with data collection techniques through document studies, semi-structured interviews with related parties, and field observations. The results indicate procedural inconsistencies in the registration of reports that do not include detailed alleged violation points, which potentially cause confusion in the follow-up process by Gakkumdu. This study recommends the need for standardized reporting formats and strengthened coordination among election law enforcement agencies to improve the effectiveness of violation handling.